Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1063/1.1644108
|View full text |Cite
|
Sign up to set email alerts
|

Tractable molecular theory of transport of Lennard-Jones fluids in nanopores

Abstract: We present here a tractable theory of transport of simple fluids in cylindrical nanopores, which is applicable over a wide range of densities and pore sizes. In the Henry law low-density region the theory considers the trajectories of molecules oscillating between diffuse wall collisions, while at higher densities beyond this region the contribution from viscous flow becomes significant and is included through our recent approach utilizing a local average density model. The model is validated by means of equil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
152
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(163 citation statements)
references
References 32 publications
11
152
0
Order By: Relevance
“…[25,26,27,28,29,30,31,32,33,34]). Such systems show the interesting feature of non-diffusive behavior of tracer particles, which stimulated experimental (see, e.g., Refs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[25,26,27,28,29,30,31,32,33,34]). Such systems show the interesting feature of non-diffusive behavior of tracer particles, which stimulated experimental (see, e.g., Refs.…”
Section: Introductionmentioning
confidence: 99%
“…Such systems show the interesting feature of non-diffusive behavior of tracer particles, which stimulated experimental (see, e.g., Refs. [33,34]) and numerical [27,29,30,31] interest. Here we present a lattice model for ultrathin films in which multiple occupancy of a site is allowed (generalizing the single-occupancy model of Refs.…”
Section: Introductionmentioning
confidence: 99%
“…The gas travels with speed between collisions and loses all the momentum when colliding on the wall. This model is a more recent development in mass transfer theory by Bhatia et al [78,79]. From Newton's law,…”
Section: Oscillator Modelmentioning
confidence: 98%
“…Recently, we have demonstrated Nicholson 2002, 2003;Bhatia et al 2004Bhatia et al , 2005) that the transport flux can be expressed as a combination of two momentumtransfer processes: that between fluid molecules --associated with viscous phenomena --and that between the fluid and the surface --associated with friction. The latter involves the population of molecules vibrating around the minimum of the adsorption potential well, with wall collisions occurring as molecular trajectories are reversed in the steeply repulsive side of this minimum.…”
Section: Introductionmentioning
confidence: 98%
“…The model has been tested against simulation in model pores with ideal diffuse reflection at the surface, as first proposed by Knudsen in discussing his classical experiments on gas flow in glass capillaries. With more realistic, atomically detailed, surfaces, it has been found that the ideal diffuse reflection hypothesis is not valid (Arya et al 2003a,b;Bhatia et al 2004;Bhatia et al 2005;Skoulidas et al 2002;Sokhan et al 2001;Sokhan and Quirke 2004). Indeed, it is very far removed from the behaviour observed for smooth graphitic surfaces, where the molecular reflection condition is close to being specular in nature.…”
Section: Introductionmentioning
confidence: 99%